A Novel Implementation Elliptic Curve Cryptography for Security Purpose - P. Ramadevi (International Journal of Control and Automation, 2019)
With the expansion of network-wide information exchange and Internet storage of sensitive data, cryptography is an increasingly vital component of network security. Numerous cryptographic algorithms, such as shared-key and public-key cryptosystems, are intended to secure information. Nevertheless, regardless of the type of cryptosystem employed, the security of the system is primarily dependent on the secrecy of the shared key deployed by the user. In general, many users employ brief keys for ease of recall. This results in data vulnerability. Integration of biometrics and cryptography is the solution to this type of problem in the current scenario.The algebraic structure of elliptic curves over finite fields forms the basis of elliptic curve cryptography (ECC), a method of public-key cryptography. Lenstra elliptic curve factorization is one of numerous integer factorization methods with uses in cryptography that rely on elliptic curves. The goal of a secure crypto processor is to serve as the security sub-system's backbone, rendering physical safeguards unnecessary for the rest of the sub-system. A 256-bit ECC public key, for example, should provide comparable security to a 3072-bit RSA public key, which is the primary promise of ECC. Furthermore, ECC promises to reduce storage and transmission requirements while maintaining the same level of security as an RSA-based system with a large modulus and correspondingly larger key. The advantages of elliptic curve cryptography (ECC) (as a public key cryptography system) have led to its use in a number of contemporary applications. The primary benefit of ECC is that it uses smaller key sizes while providing security on par with other methods.